1993
DOI: 10.1126/science.261.5118.192
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation by Interacting Chemical Fronts

Abstract: Experiments on a bistable chemical reaction in a continuously fed thin gel layer reveal a new type of spatiotemporal pattern, one in which fronts propagate at a constant speed until they reach a critical separation (typically 0.4 millimeter) and stop. The resulting asymptotic state is a highly irregular stationary pattern that contrasts with the regular patterns such as hexagons, squares, and stripes that have been observed in many nonequilibrium systems. The observed patterns are initiated by a finite amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
305
1
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(325 citation statements)
references
References 17 publications
10
305
1
4
Order By: Relevance
“…Newman has suggested that Turing-type reaction-diffusion systems known to spontaneously generate stable spatial patterns of chemical-concentration peaks and valleys could account for patterns of chondrogenesis arising from a homogeneous population of limb mesenchymal cells both in vivo and in vitro (Newman, 1988(Newman, , 1993Newman and Frisch, 1979;Newman et al, 1988;Newman and Comper, 1990;Leonard et al, 1991). Indeed chemical patterns strikingly similar to the chondrogenic patterns in limb mesenchymal cultures have been obtained experimentally in purely chemical systems (Castets et al, 1990;Lee et al, 1993).…”
Section: Region-dependent Chondrogenic Capacity Of Wing-bud Mesenchymementioning
confidence: 91%
“…Newman has suggested that Turing-type reaction-diffusion systems known to spontaneously generate stable spatial patterns of chemical-concentration peaks and valleys could account for patterns of chondrogenesis arising from a homogeneous population of limb mesenchymal cells both in vivo and in vitro (Newman, 1988(Newman, , 1993Newman and Frisch, 1979;Newman et al, 1988;Newman and Comper, 1990;Leonard et al, 1991). Indeed chemical patterns strikingly similar to the chondrogenic patterns in limb mesenchymal cultures have been obtained experimentally in purely chemical systems (Castets et al, 1990;Lee et al, 1993).…”
Section: Region-dependent Chondrogenic Capacity Of Wing-bud Mesenchymementioning
confidence: 91%
“…Turing patterns in a chemical reactor were first experimentally observed by De Kepper's group in a chlorite-iodide-malonic acid (CIMA) reaction [18] and later confirmed by Ouyang and Swinney who observed striped as well as spotty patterns [53]. The chance to experimentally detect Turing structures has produced a renewed interest in these systems as shown by the large number of theoretical [35,58], computational [43,44,67] and experimental studies in the field [6,42,52].…”
Section: Introductionmentioning
confidence: 93%
“…Spatially distributed reaction networks can support a variety of different spatiotemporal nonequilibrium states, including target patterns, spiral waves and other stationary inhomogeneous states such as labyrinthine patterns and linked and knotted chemical domains 32, 33. Turing patterns in the form of stripes and spots,34 and domains in bistable chemical media with competing interactions35 have been observed in early laboratory experiments. Alternatively, the chemical patterns could be produced by fabricating domains of catalyst on a surface that promote the production of fuel from reactions in the medium 36.…”
Section: Introductionmentioning
confidence: 96%